Preliminary Study: Effect of Infrared Soft-Laser Irradiation on Gonadal Maturity Stage of Female Siamese Striped Catfish (Pangasianodon hypophthalmus) - Puspitasari, Febriyanti; Mukti, Akhmad Taufiq; Mubarak, Ahmad Shofy (Department of Aquaculture, 2025)
Gonadal maturity and spawning of Siamese striped catfish depend on the rainy season, while outside of the season, hormonal treatment is not effective. Alternative technologies should be explored to enhance the gonadal maturity of fish. This study aims to examine the effect of infrared soft-laser irradiation on the gonadal maturity stage (GMS) of female Siamese striped catfish (Pangasianodon hypophthalmus). This study was performed through experimental methods using a completely randomized design (CRD) consisting of six treatments with four replications. Treatments were used, namely negative control (K-, no treatment), positive control (K+, injection of human chorionic gonadotropin / hCG and ovaprimTM), soft-laser exposure dose of 0.2 J/cm2 (T1), 0.4 J/cm2 (T2), 0.6 J/cm2 (T3), and 0.8 J/cm2 (T4). The parameter of GMS was measured. Data was analyzed using ANOVA following Duncan’s multiple range test. The result showed that soft-laser irradiation showed significant differences (P < 0.05) in GMS of female Siamese striped catfish. The highest GMS was shown through soft-laser exposure dose of 0.4 J/cm2 (T2), with 98.75% of fish reaching GMS IV and 1.25% at GMS III. Infrared soft-laser irradiation dose of 0.4 J/cm2 was the optimal dose to accelerate the gonadal maturity of female Siamese striped catfish.